Faktor-faktor yang Memengaruhi Implementasi Transformasi Digital Pada Bank XYZ: Factors Affecting The Implementation of Digital Transformation at Bank XYZ - Elsi Elfrida; Popong Nurhayati; Imam Teguh Saptono (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Increasingly high demands for digital acceleration and more digitally savvy societal behavior make digital transformation a strategy to improve company performance. This study aims to analyze the influence factors of strategic formulation, leadership, organizational culture, organizational structure change, resources, monitoring, communication, and technology on the implementation of digital transformation to further formulate strategies for strengthening the implementation of digital transformation that can be carried out by Bank XYZ. The study involved 85 respondents who were involved in the transformation team and five expert respondents. The results of the SEM-PLS analysis show that seven of the eight factors, namely strategy formulation, leadership, organizational culture, resources, monitoring, communication, and technology, have a positive and significant effect on the implementation of digital transformation, while the organizational structure change has no effect. The strategy for strengthening the implementation of digital transformation was analyzed using the Analytical Hierarchy Process (AHP) with the results showing that the leadership factor is a priority in strengthening the implementation of digital transformation. In line with this, the priority actor mapping analysis is the business directorate, and the goal of implementing digital transformation that is a priority is to increase productivity. Thus, the best alternative strategy that can be applied to strengthen the implementation of digital transformation is to sharpen KPIs on the outcome side so that the success and contribution of digital initiatives to the business as usual can be tracked. Keywords: AHP, digital transformation, SEM PLS, strategy implementation, business as usual